Determinants of Employee Performance: The Roles of Human Resource Quality, Welfare, Work Motivation, Discipline, and Work Ethics in the Secretariat of Semarang City Regional House of Representatives - Dinda Ari Ayu Isnani; Sarsono; Siti Maryam; Fithri Setya Marwati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This study aims to analyze the influence of human resource quality, employee welfare, work motivation, work discipline, and work ethics on employee performance at the Secretariat of the Regional House of Representatives (DPRD) of Semarang City. Employee performance has become an important issue in improving the quality of public services and strengthening organizational effectiveness in government institutions. This study employed a quantitative research approach using primary data collected through questionnaires distributed to employees of the Secretariat of DPRD Kota Semarang. The research sample consisted of employees selected using a saturated sampling technique. Data were analyzed using multiple linear regression after fulfilling the classical assumption tests, including validity, reliability, normality, multicollinearity, and heteroscedasticity tests. The findings indicate that human resource quality, work motivation, work discipline, and work ethics have positive and significant effects on employee performance. Conversely, employee welfare does not significantly affect employee performance. Simultaneously, all independent variables significantly influence employee performance. These findings imply that government institutions should prioritize improving employee competencies, strengthening work discipline, fostering positive work ethics, and enhancing work motivation to improve organizational performance. The results contribute to the development of human resource management literature, particularly in the context of public sector organizations. Kata kunci: Human resource quality; employee welfare; work motivation; work discipline; work ethics; employee performance.